Aportes da arquitetura corporativa para o ambiente dos sistemas informatizados de gestão arquivística de documentos: aplicação em companhia de energia elétrica - Fernando Hadad Zaidan (2015)
The aim of this research is to understand the contributions that the enterprise architecture (EA) provides to the records management systems (RMS) environment for the organizations in general. It is the RMS role to process the set of operations of records managements (RM) life cycle: production, conduction, use, evaluation, archiving and destination of records. Due to the current complexity of the businessscenario, applications and information technologys (IT) infrastructure, it is recommended the creation of an EA in order to achieve a holistic view of the organization and ease the comprehension of the systems structures and behaviors. The use of EA adds to the business the Strategic Alignment of Information Technology. In order to orient this research we adopted the design science (DS) methodology and the design science research (DSR) method. Although the DS paradigm is used to guide scientific researches about information, technology,engineering and management, it is rarely used in the Information Science field. The use of DS and DSR generates knowledge in the process of artifact creation in the case of this research, the EA models. In addition to this methodology choice, we utilize qualitative research, literature review, direct observation, documents collection, and interviews. A distinct element in this work was the possibility to immerse the researcher in the course of a research and development (R&D) project in the electric power company Companhia Energética de Minas Gerais (CEMIG). With a two year deadline, this R&D project was created in CEMIG in 2013 in order to attend the needs to improve the process known as Batch Cover Management. This management performs procedures and technical operations of the accounting documents from CEMIG in an integrated way. After investigating the RMs problems, as results, the EA models were developed, presented and discussed in the current and future RMS environment. In the theoretical point-of-view, we presented EA contributions to the RM in the R&D project and to the organizations in general. In the practical approach, through the redesign and validation of the models, we confirmed a greater alignment between the planned RMS and CEMIGs business strategies.